Family Perception of Diseases Related to the Reference Time in Stroke Patient: Literature Review - Putri, Zelin Resiana; Santoso, Bagus Rahmat (Journal Of Nursing Practice, 2020)
Background: Stroke is a functional brain disorder characterized by neurological deficits or nerve paralysis that occurs suddenly due to obstruction of blood flow to the brain. In 2018 the prevalence of stroke in Indonesia has increased compared to 2013, namely the prevalence of stroke rose from 7 percent to 10.9 percent. South Kalimantan ranks 5th in Indonesia with a stroke prevalence of 12.7%. The duration of stroke is caused by the delays in referring patients to the hospital. Poor perception is one of the factors that causes delay in patients being taken to the hospital for immediate treatment.   Purpose: This study aimed to learn about family perceptions of diseases related to patient referral in Empirical studies in the past 5 years. Methods: This study uses the literature review method. a database with the electronic search on Ebsco, ProQuest, Google Scholar, and DOAJ that published in 2016-2019. Results: There is a correlation between the perception of the disease with referral time in stroke patients. Lack of knowledge about the symptoms of stroke symptoms that arise so that the perception of symptoms that arise is an ordinary disease and can disappear by itself. Conclusion: Closely Banjar culture causes families to choose to only bring patients to traditional medicine rather than bringing stroke patients to the hospital. The family has the perception that stroke is a common disease that can be cured by bringing patients to traditional medicine